The Evolution of Sustainability and Socio-Economic Functions of National Pension Systems - Antokhonova, Inna V.; Briukhanova, Valentina B.; Mikhaylova, Svetlana S. (International Journal of Economics and Financial Issues, 2015)
The development of the national pension system is connected with the coherence of the economic interests of the main participants concerning the storage, redistribution and use of premiums. The relationship and account of economic interests form the motivational core of a sustainable national pension system. The evolution of the stability concept in the course of time is determined by the evolution of the system of values underlying the socio-economic functions of national pension systems. The study aims to develop a model of sustainable national pension system that meets the social and economic criteria. Because of the complexity and dynamism of the object, a comparative analysis of pension systems in developed countries is carried out in order to identify key indicators and significant features of national pension systems and the definition of Russia’s place. The model of a sustainable national pension system is the result of the analysis and synthesis of the best world experience in solving the problem of stability. The article is of interest from the standpoint of analyzing the issues of national security. Keywords: national pension system, mandatory and voluntary pension insurance, pensions, redistribution mechanism, model of the pension system. JEL Classifications: H55; G23; J32